Review of International Arrangements Relating to Ownership Status of The Foreign Historical Shipwrecks in Indonesian Water - Muhammad Nur (Fakultas Hukum Universitas Mataram, 2019)
At the international level there have been international conventions that accommodate the regulation of historic sinking vessels, although only in general, namely the 1982 United Nations Convention on the Law of the Sea (UNCLOS 1982), Convention on the Protection of the Underwater Cultural Heritage 2001, International 1989 Convention on Salvage, and The United Nations Convention on the Means of Prohibiting and Preventing the Illicit Import, Export and Transfer of Ownership of Cultural Property 1970. However, if you see the contents of the regulation from the international provisions, it seems that there is no firmness regarding the legal owner of the historic sinking vessel in Indonesia. This study uses a normative juridical research method by examining library materials or other secondary materials. The data collection method used is the literature study. The tool used is a document in the form of primary, secondary and non-legal materials. The data obtained were analyzed qualitatively then presented descriptively.